Plantas de cobertura em sistema de plantio direto agroecológico de hortaliças na região oeste do Paraná - Zang, Andressa Caroline (2022)
Green fertilizers and cover crops have been used over the years, enabling the conservation and improvement of the chemical, physical and biological attributes of the soil. Due to their agronomic and phenological characteristics, land cover plants are presented as fundamental components to enable the use and sustainable management of the soil and the production of quality food. Thus, the objective of this study was to evaluate the performance of summer cover crops in the supply of dry matter to the soil and its effects on the culture of broccoli and exchange zucchini and the microbiological activity in an agroecologically based Direct Vegetable Planting System (SPDH) in the Western region of Paraná. The work was developed at the Horticulture Teaching and Research Unit of the Federal Technological University of Paraná (UTFPR), Santa Helena Campus, where the design used was randomized blocks, with eigth treatments and three replications. The treatments consisted of cover crops, as follows: black-bean (Mucuna aterrima); jack beans (Canavalia ensiformis); Crotalaria-espectabilis (Crotalaria spectabilis); Crotalaria-ochroleuca (Crotalaria ochroleuca); Dwarf-pigeon-pea (Cajanus cajan); Millet (Pennicetum glaucum) and two witnesses without soil cover, consisting of fallow with conventional soil preparation and fallow with mowing. The parameters evaluated consisted of: initial development and the rate of land cover by the cover crops; determination of the cycle (days) from emergence to flowering/management; contribuition of plant dry matter to soil cover; decomposition of cover crops through litter bags; estimation of the respiratory activity of soil microorganisms; agronomic characteristics and total productivity of vegetable crops. In the cover crops, the millet showed a rapid soil cover in 35 days after emergence (DAE) and good biomass production, reaching more than 15 t ha-1, higher than black-bean (5,7 t ha-1 ) and dwarf-pigeon-peas (5,4 t ha-1). Broccoli showed productivity close to the nacional average of 17,2 t ha-1 of MV and 1,4 t ha-1 of MS. For zucchini, the average productivity was 1,908 kg plant-1 and total 23.8 t ha-1. For plants os commercial interest, jack beans had the best performance over crops. The treatments did not show negative results to crops of commercial interest, with high productivity in SPDH.